Adjuvant Effect of Cationic Liposomes for Subunit Influenza Vaccine: Influence of Antigen Loading Method, Cholesterol and Immune Modulators - Barnier-Quer, Christophe (MDPI, 2013)
Cationic liposomes are potential adjuvants for influenza vaccines. In a previous study we reported that among a panel of cationic liposomes loaded with influenza hemagglutinin (HA), DC-Chol:DPPC (1:1 molar ratio) liposomes induced the strongest immune response. However, it is not clear whether the cholesterol (Chol) backbone or the tertiary amine head group of DC-Chol was responsible for this. Therefore, in the present work we studied the influence of Chol in the lipid bilayer of cationic liposomes. Moreover, we investigated the effect of the HA loading method (adsorption versus encapsulation) and the encapsulation of immune modulators in DC-Chol liposomes on the immunogenicity of HA. Liposomes consisting of a neutral lipid (DPPC or Chol) and a cationic compound (DC-Chol, DDA, or eDPPC) were produced by film hydration-extrusion with/without an encapsulated immune modulator (CpG or imiquimod). The liposomes generally showed comparable size distribution, zeta potential and HA loading. In vitro studies with monocyte-derived human dendritic cells and immunization studies in C57Bl/6 mice showed that: (1) liposome-adsorbed HA is more immunogenic than encapsulated HA; (2) the incorporation of Chol in the bilayer of cationic liposomes enhances their adjuvant effect; and (3) CpG loaded liposomes are more efficient at enhancing HA-specific humoral responses than plain liposomes or Alhydrogel.